Genetic diversity of spotted scat (Scatophagus argus) in Vietnam based on COI genes - Huy Van Nguyen; Minh Tu Nguyen; Nghia Duc Vo; Nguyen Thi Thao Phan; Quang Tan Hoang (Fisheries and Aquatic Sciences, 2022)
A spotted scat, Scatophagus argus, has a high nutritional value and is among Asia’s most widely consumed fish species. Thua Thien Hue’s consumption market considers this species to be of high economic value and requires protection and conservation of the population. However, the studies on the identification and genetic diversity of S. argus distributed in Vietnam are still lacking. Therefore, mitochondrial cytochrome c oxidase subunit I (COI) gene was utilized to distinguish different populations and investigate the genetic diversity of two populations of S. argus from Tam Giang lagoon, Thua Thien Hue province (n = 31) and Ca Mau province (n = 14). The sequencing results indicated 13 distinct haplotypes among 45 sequences. Five single nucleotide polymorphisms were observed to distinguish Hue spotted scat population. The S. argus population in Ca Mau province was higher haplotype diversity (Hd) and nucleotide diversity (π) than those of Thua Thien Hue province, which demonstrates that there are minor differences between haplotypes. There were genetic distances ranging from 0%–4% within the populations and 6.67% between the two populations. In addition to the sequencing, the comparison of morphology, biology, culture, and the growth rate was sufficient to distinguish the spotted scat S. argus in Thua Thien Hue from Ca Mau.